Development and Validation of a Computer-Aided Instructional Manual in Science, Technology and Society (STS)for the Revised General Education Curriculum in Higher Education (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
Technology is now widely used in the education system. Varieties of online resources are available and continuously updated. A new course which is part of the General Education Curriculum for the first batch of Senior High School (SHS) graduates is in Science, Technology, and Society (STS). With the nature of the subject, references of the released syllabi for STS can mostly be found online for powerpoint presentations, short clips, and movies. The researcher came up with this study to device a computer-aided instructional material to deliver the Science, Technology, and Society (STS) course effectively and confidently. This study uses a descriptive-evaluative type of research to determine the level of acceptability, content validity and recommendations of the proposed computer-aided instructional manual to the forty (40) science teachers of Higher Education Institutions (HEIs) in Quezon City. Data was gathered through a survey questionnaire. The significant difference in the level of content validity and acceptability on the developed computer-aided instructional material in teaching Science, Technology, and Society (STS) considering the respondent’s profile was also tested. The result on the level of content validity in objectives, topics, concepts, directions, activities, and reflection, the computed P-values of all profiles show greater than 0.05 level of significance thus the null hypothesis is accepted except for the P-value for employment status in objectives which is 0.033 and topics which is 0.036, thus the null hypothesis is rejected. The result on the level of acceptability in clarity, usefulness, language, and style, illustration, presentation and evaluation, the computed P-values of all profiles show greater than 0.05 level of significance thus the null hypothesis is accepted except for the P-value for employment status in clarity which is 0.036, language and style which is 0.030 and illustration which is 0.015, thus the null hypothesis is rejected. The overall recommendation of the acceptability of the computer-aided instructional manual has a weighted mean of 4.30 which is interpreted as high. The use of this computer-aided instructional material may benefit the teachers as they are also encouraged to suggest additional topics and links to update the instructional material’s content. Assessment tools may also be incorporated by the teacher as they use this instructional manual especially the use of rubrics which are appropriate for student’s outcome-based education.
Keywords: development, validation, computer-aided instruction, science, technology and society